SMU partners with Google to nurture future-ready analytics talent to meet industry demand - Singapore Management University (Institutional Knowledge at Singapore Management University, 2019)
Singapore Management University (SMU) and Google Singapore have signed an agreement to offer the SMU-Google Squared Data & Analytics Programme (‘SMU-Google Squared Programme’) to SMU’s undergraduate students. This partnership marks the first time that Google is extending its Google Squared Data & Analytics Programme to the undergraduates of a local university.